Dietary Supplementation through pulses for nutritional security - Singh, Ummed; Verma, Prasoon; Praharaj, C S; Srivastava, R P; Parihar, A K (Indian Farming, 2018)
Pulses are essentially rich in vitamins and minerals such as folate, iron, calcium, magnesium, zinc and potassium. The main role of pulses, of course, is to fulfill protein needs of dominant vegetarian population of India. Proteins present in pulses are also complementary to the amino acid groups present in cereals. Therefore, combination of cereals and pulses in a diet makes a nutritionally complete vegetarian food. Among the pulses, pigeonpea, chickpea, urdbean, mungbean, lentil, rajmash, lathyrus, fieldpea etc. are grown in Indian subcontinent extensively round the year